A Real Casa Pia de Correcção e Educação do Porto : 1792-1804 - Santos, Maria José Moutinho (2001)
In the year of 1794, Francisco de Almada e Mendonça received royal accent andthe financial support to found in Oporto a social institution, dedicated to the correction and education, taking as a model the Casa Pia de Lisboa, which has been created by Pina Manique. In these pages, we analyse the scope and contents of this project which was never brought to completion.